An Analysis of the Challenges and Strategies to Improve and Strengthen the Employment Status of Persons with Disabilities in Asia - Ryuhei Sano (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M) Institut Bisnis dan Komunikasi LSPR, 2021)
Over the past few decades, the employment of persons with disabilities in the Asia region has been the subject of the spotlight of several studies from various government and non-government organizations. A proper and thorough look at the employment status of persons with disabilities is a crucial aspect in the overall improvement of their rights in society, especially in terms of being free from discrimination by having equal access to decent work along with other members of society. Several transformations have occurred in the employment status of persons with disabilities. With growing potential being seen in the current world work atmosphere, persons with disabilities, with the help of technological advances, the popularity of the so-called Gig Economy, and expanding entrepreneurial spirit of the populace, the door seems to be opening wider for persons with disabilities. Given this current picture of what is happening in Asia, this paper will look at the growth of employment of persons with disabilities and its causes; the current realities and challenges, as well as possible directions that this trend is taking; and the effective strategies to further develop and promote employment of persons with disabilities.